Raynaud’s Phenomenon Impact on Quotidian Quality of Life - Taylor, Isobel; Silva, Ivone; Barreto, Susana; Soares, César; Mendes, Joaquim (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Objective: To gain further understanding into the needs of Raynaud’s phenomenon (RP), patient questionnaires were conducted in England, UK 2017 at an SRUK patient conference and Porto, Portugal 2018 at Central Hospital Universitário Porto (CHUP). The questions focused on daily activities and experience. Method: Sixty-four participants answered questions on their daily experience with RP, specific and general. Analysis grouped results into topics quantified by number and %. Results: Although many tasks trigger RP episodes, some are more problematic than others, e.g. peeling vegetables; for many, the pain (46.9%) is not the worst part, but instead the hinderance in function, inability (73.4%) especially regarding hands and fingers. Conclusion: A Design Specification (DS) criteria for RP patients’ hands is formed through the listed activities. The key needs identified for RP patients fingers and hands are maintenance of: Dexterity, Tactility and Comfort whilst cohering to aesthetic needs & wellbeing.